1992
DOI: 10.1136/gut.33.5.678
|View full text |Cite
|
Sign up to set email alerts
|

Increased pulmonary and intestinal permeability in Crohn's disease.

Abstract: We tested the hypothesis that an increased epithelial permeability may affect sites other than the intestine in patients with Crohn's disease by simultaneously evaluating their pulmonary and intestinal permeability. Pulmonary and intestinal permeability were measured by clearance of inhaled technetium99m diethylene triamine pentacetate (99mTc-DTPA) and by urinary recovery of chromium-51 ethylene diamine tetracetate respectively in 22 patients with Crohn's disease. The half time clearance of 99mTc-DTPA from lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 35 publications
(1 reference statement)
2
42
0
2
Order By: Relevance
“…An increased frequency of asymptomatic bronchial hyperresponsiveness has been reported in patients with Crohn's disease, and a subclinical accumulation of activated T lymphocytes has been demonstrated in the lung of patients with Crohn's disease without respiratory symptoms (19,25). No study has demonstrated thus far the simultaneous presence of alveolar lymphocytosis and bronchial hyperresponsiveness to methacholine in respiratory asymptomatic patients with Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…An increased frequency of asymptomatic bronchial hyperresponsiveness has been reported in patients with Crohn's disease, and a subclinical accumulation of activated T lymphocytes has been demonstrated in the lung of patients with Crohn's disease without respiratory symptoms (19,25). No study has demonstrated thus far the simultaneous presence of alveolar lymphocytosis and bronchial hyperresponsiveness to methacholine in respiratory asymptomatic patients with Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…IP has been implicated in the pathogenesis and frequent relapses of Crohn's disease (CD) [2][3][4][5][6] . Seven to 18% higher relapse rate has been reported in patients with increased IP compared to those with normal IP [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…A number of studies have reported a relationship between abnormal IP and the activity of the disease [3,5,37,38] . In some reports it has been observed that the magnitude of alterations in L/M ratio increases with the increase in disease activity index.…”
mentioning
confidence: 99%
“…The increased rate of DTPA clearance indicates inflammation or lung insults of any cause. In two of three published papers, a significantly higher alveolar epithelial permeability was reported in IBD patients compared to healthy people [40,41]. In the third study, no evidence of abnormal lung permeability in patients with IBD was found [42].…”
Section: Epidemiologymentioning
confidence: 89%
“…Bronchial hyperresponsiveness on methacholine challenge was independent of activity, extent and time of duration of IBD [29][30][31]. Exhaled NO correlated positively with IBD activity [37][38][39], but no relation was found for alveolar epithelial per-meability measured with the use of Tc-99m DTPA aerosol scintigraphy [40,41]. Data on relationship between IBD activity and chest HRCT picture are discrepant.…”
Section: Respiratory Disease Depending On Ibd Activitymentioning
confidence: 99%